1998
DOI: 10.1038/32419
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NF-ATc transcription factor in morphogenesis of cardiac valves and septum

Abstract: In lymphocytes, the expression of early immune response genes is regulated by NF-AT transcription factors which translocate to the nucleus after dephosphorylation by the Ca2+-dependent phosphatase, calcineurin. We report here that mice bearing a disruption in the NF-ATc gene fail to develop normal cardiac valves and septa and die of circulatory failure before day 14.5 of development. NF-ATc is first expressed in the heart at day 7.5, and is restricted to the endocardium, a specialized endothelium that gives ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
459
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(477 citation statements)
references
References 25 publications
(2 reference statements)
14
459
0
4
Order By: Relevance
“…First, mRor2 is required for cardiac septal formation. Recent genetic analyses have revealed that many regulatory molecules, including growth factors, receptors and transcription factors, are involved in the development of the heart (Nagasawa et al 1996;Basson et al 1997;Li et al 1997;Tessarollo et al 1997;de la Pompa et al 1998;Ranger et al 1998;Schott et al 1998;Tachibana et al 1998; reviewed in Burn & Goodship 1996;Lyons 1996;Rossant 1996;Barinaga 1998), although in general their roles are not restricted to septal formation. Interestingly, defects of the cardiac septum have been, thus far, the major abnormality observed in the cardio-vascular system of mRor2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…First, mRor2 is required for cardiac septal formation. Recent genetic analyses have revealed that many regulatory molecules, including growth factors, receptors and transcription factors, are involved in the development of the heart (Nagasawa et al 1996;Basson et al 1997;Li et al 1997;Tessarollo et al 1997;de la Pompa et al 1998;Ranger et al 1998;Schott et al 1998;Tachibana et al 1998; reviewed in Burn & Goodship 1996;Lyons 1996;Rossant 1996;Barinaga 1998), although in general their roles are not restricted to septal formation. Interestingly, defects of the cardiac septum have been, thus far, the major abnormality observed in the cardio-vascular system of mRor2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing cardiovascular system, calcineurin signaling is required for cardiomyocyte maturation and function as well as early vascular development. During heart chamber formation, calcineurin signaling and NFATc1 function are required for valvuloseptal development, and calcineurin signaling also has been implicated in compaction of the ventricular myocardium (de la Pompa et al, 1998;Ranger et al, 1998;Shou et al, 1998;Guo et al, 2002). In the adult heart, calcineurin signaling has a central role in cardiac hypertrophy (Bueno et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted mutagenesis of specific NFAT family members revealed additional requirements for calcineurin/NFAT signaling in the developing heart. Loss of NFATc1 results in embryonic lethality due to defects in cardiac valvuloseptal development (de la Pompa et al, 1998;Ranger et al, 1998). Embryos lacking both NFATc3 and NFATc4 have embryonic lethal cardiac metabolic defects and exhibit abnormalities in vascular maturation (Graef et al, 2001a;Bushdid et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Four members of the family have been identified, NFATc1, NFATc2, NFATc3 and NFATc4. NFATc1 and NFATc2 are the predominant members in T cells, but they are also expressed in a large variety of tissues including heart, neurons, vascular cells, chondriocytes, and adipocytes [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%